A imunidade material do advogado como corolário dos direitos da cidadania - Bertoluci, Marcelo Machado (2018)
The present thesis, developed in the area of Criminal Violence System, aims to sustain the importance, for advocacy and citizenship, of the defense and improvement of the prerogatives guaranteed to the lawyer by the Brazilian legal system, in relation to their acts and manifestations in court or outside it, as long as they are linked to the defense of the assumed cause. Among the ways to promote the reinvigoration of the profession in society, it’s proposed the reform art. 133 of the Federal Constitution, through the inclusion of a single paragraph, ensuring criminal and civil immunity for acts and manifestations against the risks that its undue flexibilization represents for the professional performance and, therefore, for the citizens' rights of defense. Placing advocacy as an intrinsic element of citizenship, the study analyzes the period that goes from the emergence of advocacy as an eminently private activity until the recognition of its public function, due to its historical action in favor of the democratizing processes of the country. It demonstrates that professional prerogatives are designed to strengthen the link between the lawyer and the citizen – or, said in another way, between advocacy and citizenship –, so that the legal protection provided by the legal system to the defenders does not convey a class privilege, but represents an authentic collective interest. Those who seek to weaken free advocacy attack the Democratic State of Law itself, and must be restrained by constitutional order. Thus, it is imperative to confer clarity, concreteness and maximum effectiveness on the criminal and civil immunity of lawyers for acts and manifestations, since it is guaranteed in favor of citizens.